CRITERIA FOR USING A ONE-DIMENSIONAL HYDRODYNAMIC MODEL FOR TWO BARRAGES SITUATED IN MEDITERRANEAN REGION - Saddek, Takkouk; Casamitjana, Xavier (European Scientific Journal, ESJ, 2013)
In order to characterise the barrage regime is usually very important to check the validity of assumptions on which its application is based. Accordingly, in this study we have estimated a set of numbers comprising the Lake number, the Wedderburn and Burger numbers, and inflow and outflow Froude numbers. Therefore we have used two years worth of time series data (2000-2001) consisting of temperature profiles, morphometry data, meteorological data, and inflow and withdrawal data of two reservoir located in the Mediterranean region.